Video-head impulse test in superior canal dehiscence. (4th May 2021) - Mukherjee, Payal; Chiarovano, Elodie; Cheng, Kai; Manzari, Leonardo; McGarvie, Leigh A.; MacDougall, Hamish G.
Abstract: Background: Superior Canal Dehiscence is classically diagnosed with typical abnormalities on Vestibular Evoked Myogenic Potentials (VEMPs) and Computed Tomography (CT) scans. Aim: This paper discusses the utility of the video Head Impulse Test (vHIT) in SCD. Methods: Data from 11 ears (8 patients) with SCD were retrospectively reviewed. Results from vHIT, VEMPs and CT and when possible, MRI scans were correlated. An audit of 300 vHIT from patients undergoing routine testing for any neurotological complaint was also conducted to look at the incidence of isolated abnormal superior canal function. Results: 82% of patients (9 ears) with SCD showed abnormal vHIT (reduced gain and catch-up saccades) isolated to the affected superior semicircular canal. Conclusion: Correlation of the CT and VEMPs are important in forming a diagnosis of SCD. However, if isolated superior canal vHIT abnormalities are demonstrated, it is suggestive of SCD and such patients should be referred for further investigations.